Role of podoplanin expression in deciding the invasive potential of ameloblastoma – A retrospective IHC study - Sindhu M. Ganvir; Pratima G. Khobragade; Swati A. Bamane; Ramnivas Kumavat; Amit Dalmia (Journal of Oral Biology and Craniofacial Research)
Background: The aim of this study was to investigate the podoplanin expression in epithelial odontogenic tumors both non-aggressive and aggressive, tumors with and without ectomesenchyme and remnants of the odontogenic epithelium from dental follicles (DF) of unerupted teeth and to examine its role in progression and invasion of tumors. Method: Thirty paraffin embedded specimens AM (15 were non-aggressive ameloblastomas and 15 ameloblastoma showing aggressive behavior), 15 paraffin embedded specimens of AOT, 15 paraffin embedded specimens of CEOT, 15 paraffin embedded specimens of CCOT were obtained and were analyzed by immunohistochemistry using anti-human podoplanin. Podoplanin expression in odontogenic epithelial cells was evaluated using a scoring method, along with calculation of the percentage of positive odontogenic cells. Results: Podoplanin was expressed strongly at the invasive front (in the peripheral odontogenic epithelial cells) of most tumors and dental follicles. Membranous expression of podoplanin in ameloblastomas was stronger in cases of ameloblastomas showing aggressive behavior than (NA) non-aggressive ameloblastomas. Conclusion: Expression of podoplanin at the invasive front (in peripheral cells) of odontogenic tumors considered to be associated with neoplastic odontogenic tissues. This molecule might play a role in progression and local invasion of odontogenic tumors. The migration and invasion mediated by podoplanin in odontogenic tumors could be related to cytoskeletal reorganization.